Oxetanes: formation, reactivity and total syntheses of natural products - Peter Gabko; Martin Kalník; Maroš Bella (Beilstein Journal of Organic Chemistry, 2025)
Oxetanes are 4-membered cyclic monoethers which have found important applications in medicinal chemistry as polar and metabolically stable isosteric replacements for gem-dimethyl and carbonyl groups. This work reviews possible synthetic strategies towards these strained heterocycles, covering both de novo constructions of the 4-membered ring as well as derivatisations of oxetane building blocks, then reactivity of oxetanes in terms of ring-opening and ring-expansion reactions, and finally total syntheses of selected oxetane-containing natural products. The literature review primarily covers reports made after the year 2015, but a few older contributions that were considered relevant are also discussed.